Heterocyclic Azo Compounds, Synthesis, Characterization, Evaluation as Antimicrobial, and Theoretical Study - Mohammed, Mohammed K.; Al-Jaber, Afrah A.; Al-Asadi, Rafid H.; Dhaef, Hawraa K. (Science and Technology Indonesia, 2026)
Five azo compounds, including N-(3-hydroxyphenyl) maleimide, were synthesized and characterized using FT-IR, 1H-NMR, 13C-NMR, and mass spectroscopy. The compounds were evaluated for antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa using the disk diffusion method. The screening results showed that the azo compounds tested were effective against the bacteria tested, particularly Staphylococcus aureus. The geometry optimization of the molecular structures and the energy calculations for compounds 1-5 were performed using the density functional approach. Molecular docking was conducted to examine the interaction of the synthesized compound 1 with two bacterial receptors and one viral receptor (neuraminidase). It was found that they would target the PDB:4CJN protein, for which the compound yielded the lowest binding energy.